An Indochinese Dominion: L'Effort indochinois and Autonomy in a Global Context, 1936–1939. Issue 2 (1st June 2020) - Edwards, M. Kathryn
Abstract: Across the French Empire, the interwar period was critical to the political mobilization that would come to drive the struggles for independence in the post-1945 era. In French Indochina, and especially in its three Vietnamese regions, dynamic debates over reform, modernization, and the colonial relationship with France marked this period. Reformers included integrationists seeking a closer rapport with France, separatists seeking complete independence, and autonomists seeking a middle ground between the two. The advent of the Popular Front in June 1936 acted as a catalyst for reformers of all stripes, who hoped that the new regime would live up to its progressive credentials. This article explores the case for Indochinese autonomy through an analysis of the French-language Vietnamese newspaper L'Effort indochinois, which was founded in October 1936. It explores the domestic and global frameworks of this campaign, and it demonstrates how foreign models of autonomous states like Canada and foreign threats to Indochinese security fundamentally shaped L'Effort' s demands for Indochinese autonomy. It further seeks to contribute to the existing scholarship on the diversity of the Vietnamese reformist landscape on the eve of decolonization.